A Single Perioperative Injection of Dexamethasone Decreases Nausea, Vomiting, and Pain after Laparoscopic Donor Nephrectomy - Shigeyoshi Yamanaga; Andrew Mark Posselt; Chris Earl Freise; Takaaki Kobayashi; Mehdi Tavakol; Sang-Mo Kang (Journal of Transplantation)
Background. A single dose of perioperative dexamethasone (8–10 mg) reportedly decreases postoperative nausea, vomiting, and pain but has not been widely used in laparoscopic donor nephrectomy (LDN). Methods. We performed a retrospective cohort study of living donors who underwent LDN between 2013 and 2015. Donors who received a lower dose (4–6 mg)  (n=70) or a higher dose (8–14 mg) of dexamethasone (n=100) were compared with 111 donors who did not receive dexamethasone (control). Outcomes and incidence of postoperative nausea, vomiting, and pain within 24 h after LDN were compared before and after propensity-score matching. Results. The higher dose of dexamethasone reduced postoperative nausea and vomiting incidences by 28% (P=0.010) compared to control, but the lower dose did not. Total opioid use was 29% lower in donors who received the higher dose than in control (P=0.004). The higher dose was identified as an independent factor for preventing postoperative nausea and vomiting. Postoperative complication rates and hospital stays did not differ between the groups. After propensity-score matching, the results were the same as for the unmatched analysis. Conclusion. A single perioperative injection of 8–14 mg dexamethasone decreases antiemetic and narcotic requirements in the first 24 h, with no increase in surgical complications.